Technology-Based Learning and Financial Literacy in Strengthening Students’ Credit Risk Assessment Skills - IGN Oka Ariwangsa; Komang Widhya Sedana Putra P; Kadek Wulandari Laksmi P (Journal of Instructional and Development Researches, 2025)
This study aims to examine how a technology-enhanced learning study model improves students’ credit risk assessment skills and to determine whether financial literacy strengthens this effect. It addresses a gap in the literature, particularly within developing economies, where limited evidence exists on the combined role of digital learning cycles and financial literacy in shaping analytical competence. A quantitative explanatory approach was employed to test the relationships among the study variables and assess the moderating role of financial literacy. Data were gathered through a structured online questionnaire administered to 200 business and finance students in Bali. The instrument consisted of 15 validated indicators measuring technology-enhanced learning study practices, financial literacy, and credit risk assessment ability. Respondents were selected using purposive sampling, focusing on students who had completed core finance-related coursework. The dataset was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate both direct and moderating effects. Reliability, validity, and model fit were assessed before hypothesis testing. The findings show that technology-enhanced learning study exerts a significant positive influence on students’ credit risk assessment ability. Furthermore, financial literacy was found to moderate this relationship, indicating that students with stronger financial literacy benefit more from iterative digital learning processes. These results support the integration of reflective technology-based learning with financial literacy development to better prepare students for analytical decision-making in financial professions.